Effect of Stocking Density and Salinity on the Survival and Growth in Nursery Rearing of Pearlspot, Etroplus Suratensis(Bloch) - Bylavi,Mohammed (School of Aquaculture and Biotechnology,KUFOS, 2014)
Abstract- Etroplussuratensis, the state fish of Kerala is endemic to peninsular India and Sri Lanka. It is considered as a good table fish and has wide salinity tolerance. The present study was performed for a period of 35 days to understand the effect of stocking density and salinity on the survival and growth of Etroplus suratensis in its nursery phase. Four different stocking densities, viz., 50, 100, 150 and 200 hatchlings per m2 (D1, D2, D3 and D4, respectively) under four different salinities of rearing water, viz., 0, 5, 10 and 15 ppt (S1, S2, S3 and S4, respectively) altogether 16 treatment combinations S1D1, S1D2, S1D3, S1D4, S2D1, S2D2, S2D3, S2D4, S3D1, S3D2, S3D3, S3D4, S4D1, S4D2, S4D3 and S4D4 were tested. The experiment was laid out in a Completely Randomized Design with three replicates for each treatment. A total of 1280 hatchlings were stocked in all the treatment combinations and the feeding was done ad libitum with formulated feed of overall protein content 36 %. The highest length increment (2±0.08 cm) was observed in treatment S2D1 and the lowest value (1.52±0.05 cm) observed in treatment S4D3. Similarly, the highest weight increment (0.49±0.005 g) was recorded in treatment S2D1 and the lowest value (0.24±0.005 g) in treatment S4D4. The fishes maintained in treatment S1D1 exhibited higher growth and survivability. The results also showed that fish growth was significantly affected by increase in stocking density and salinity. The highest Food conversion ratios were obtained from treatment S2D2 (1.47) and S2D1 (1.48). A statistical comparison of the weight and length increments in all the treatments, using ANOVA, revealed that S2D1, S2D2 and S2D3 are the best treatment combinations for nursery rearing of Etroplus suratensis.